2010
DOI: 10.1007/s11433-010-0129-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the ring-like vortices and spike structure in transitional boundary layers

Abstract: At the late stage of transitional boundary layers, the nonlinear evolution of the ring-like vortices and spike structures and their effects on the surrounding flow were studied by means of direct numerical simulation with high order accuracy. A spatial transition of the flat-plate boundary layers in the compressible flow was conducted. Detailed numerical results with high resolution clearly represented the typical vortex structures, such as ring-like vortices and so on, and induced ejection and sweep events. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…By this visualization method, the vortex structures shaped by the nonlinear evolution of T-S waves in the transition process are shown in Figure 5(A). The evolution details are studied in our previous papers [19][20][21][22][23], and the formation of ring-like vortices chains is consistent with the experimental work (see [13], Figure 5(B)) and previous numerical simulation by Bake et al [3].…”
Section: Verification and Validationsupporting
confidence: 87%
“…By this visualization method, the vortex structures shaped by the nonlinear evolution of T-S waves in the transition process are shown in Figure 5(A). The evolution details are studied in our previous papers [19][20][21][22][23], and the formation of ring-like vortices chains is consistent with the experimental work (see [13], Figure 5(B)) and previous numerical simulation by Bake et al [3].…”
Section: Verification and Validationsupporting
confidence: 87%
“…It is revealed that high-speed flows of the out layer are drawn into the near wall region by the sweeping movement. According to our research of the positive spikes [4], it is believed that these "dark spots" structures are consistent with the formation of positive spikes in the previous work. Firstly, the quasistreamwise vortex structures at the outer part of the U-shaped vortex are produced by the accumulative positive spikes, and then are connected with the head part of the ring-like vortex to generate the U-shaped vortex, and finally develop into the barrel-shaped vortex.…”
supporting
confidence: 90%
“…Therefore, this is a matter of cardinal significance in exploring the mechanism of the boundary layer transition. At the late-stage of the transition, there are complex vortex structures [3,4], including the generation of the complex ring-like vortex, which are main features at this stage. With the evolution of the vortices in the flow field, more complex new vortex structures are produced [5], and turbulent spots have arisen in regions possessing some turbulent characteristics [6], and eventually evolve into a fully developed turbulent flow [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ring-like vortices play a vital role in the transition process of the wall boundary layer flow, and its formation mechanism is very complex [26][27] . Based on our numerical results, the relationship between the generation of ring-like vortices, the primary streamwise vortices, and secondary streamwise vortices is investigated.…”
Section: Secondary Streamwise Vortices and Ring-like Vorticesmentioning
confidence: 99%